Analysis of Impulsive Buying Consumptive Behavior during the Shopee E-Commerce Double Date Event (A Study of Parents of Students at the AHE Lamongan Tutoring Institute) - Arrizqah Bariroh; Bakhrul Huda (al-Afkar, Journal For Islamic Studies, 2026)
The development of information and communication technology has brought very significant changes to human life. In the digital era, technology and the internet are increasingly developing, causing consumer behavior among society to experience a drastic increase. The ease of technology and the internet then gave birth to online shopping sites which are usually known as E-Commerce or electronic commerce. The convenience offered by E-Commerce helps people to obtain various life needs, such as secondary, primary and even tertiary needs. However, apart from the positive impact felt, people's behavior tends to become more consumptive. Without realizing it, they spend a lot of money just to buy things that are not really needed. This research aims to find out what factors encourage consumer behavior among people to increase every day. This research uses qualitative methods and a literature review. Qualitative research methods are a type of research that produces discoveries that cannot be achieved or obtained using statistical procedures or other means of quantification (measurement). The subjects of this research were 10 parents of millennial students who used the Shopee application to fulfill their lifestyle. The data collection technique used was to recruit 10 active student parents who had answered several questions via gform and met the criteria, then continued with a semi-structured interview method via the WhatsApp application with the questions asked focusing on their experiences during the twin date event. The results of this research conclude that the factors that influence Impulsive Buying consumptive behavior include promotions and discounts, ease of access, product display and advertising, free shipping and emotional involvement.